2020
DOI: 10.1093/ehjci/ehaa946.3782
|View full text |Cite
|
Sign up to set email alerts
|

CD40 levels in plasma are associated with cardiovascular disease and in carotid plaques with a vulnerable plaque phenotype and remodelling

Abstract: Background and purpose CD40 and CD40 ligand (CD40L) are costimulatory molecules and members of the TNF receptor superfamily well known for their involvement in inflammatory and autoimmune diseases. This study uses two large human cohorts – the SUrrogate markers for Micro- and Macro-vascular hard endpoints for Innovative diabetes Tools (SUMMIT) and the Carotid Plaque Imaging Project (CPIP) – to explore the potential of plasma or intra-plaque expression of CD40 and CD40L as biomarkers and to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Human data in support of the role of soluble CD40R as a marker of systemic atherosclerosis are becoming consistent. We have already reported that the expression of CD40R is high in carotid atherosclerosis plaques and correlates with the plaque lipid content, particularly with oxidized LDL (51) . More recently, through an extensive human plaque RNA expression analysis, CD40R was found to be one of the 4 most expressed proteins (52) .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Human data in support of the role of soluble CD40R as a marker of systemic atherosclerosis are becoming consistent. We have already reported that the expression of CD40R is high in carotid atherosclerosis plaques and correlates with the plaque lipid content, particularly with oxidized LDL (51) . More recently, through an extensive human plaque RNA expression analysis, CD40R was found to be one of the 4 most expressed proteins (52) .…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, by adding to conventional risk factors LDL-cholesterol the area under the curve of ROC analysis for presence of any plaque showed no significant change (from 0.7914 to 0.7910). Although the data need to be replicated in other cohorts, recent data from the SUMMIT 3-year follow-up indicate that CD40R, as a continuous variable, is an independent predictor of cardiovascular events and its concentration in plaque homogenates -collected from a different cohort -correlates with histologic indices of plaque vulnerability (51) . We acknowledge that the quantification of atherosclerosis was limited to carotid arteries, thus we cannot conclude that CD40R can actually predict the atherosclerosis burden of other territories, however atherosclerosis is frequently a systemic disease and, in fact, the presence of plaques in the carotid artery is considered also by the most recent guidelines (61) a risk modifier for cardiac events and recent studies found close associations between serum CD40R and both coronary artery (52,54) and peripheral atherosclerosis (53) .…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Plasma CD40 levels are associated with the severity of carotid AS and an increased risk for future CV events. Intraplaque levels of sCD40 and sCD40L are also associated with vulnerability and remodeling (Shami et al, 2020). The costimulatory CD40 and CD40L are implicated in the regulation of the inflammatory response during AS development.…”
Section: Macrophage-related Cytokines In Atherosclerosis Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…This highly stable and accurate immunosensor exhibited a DL of 13.1 pg/mL for sCD40L (Yuan et al, 2015). It is important to note here, that sCD40L is an important biomarker in cardio-vascular diseases as well (Shami et al, 2020) and therefore, biosensor-mediated detection of soluble isoforms of immune-checkpoint molecules has broader applications in many diseases.…”
Section: Biosensor Mediated Detection Of Soluble Immune Checkpoint Mo...mentioning
confidence: 90%